(x-5)(x+8)=8(x-2)

Simple and best practice solution for (x-5)(x+8)=8(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-5)(x+8)=8(x-2) equation:


Simplifying
(x + -5)(x + 8) = 8(x + -2)

Reorder the terms:
(-5 + x)(x + 8) = 8(x + -2)

Reorder the terms:
(-5 + x)(8 + x) = 8(x + -2)

Multiply (-5 + x) * (8 + x)
(-5(8 + x) + x(8 + x)) = 8(x + -2)
((8 * -5 + x * -5) + x(8 + x)) = 8(x + -2)
((-40 + -5x) + x(8 + x)) = 8(x + -2)
(-40 + -5x + (8 * x + x * x)) = 8(x + -2)
(-40 + -5x + (8x + x2)) = 8(x + -2)

Combine like terms: -5x + 8x = 3x
(-40 + 3x + x2) = 8(x + -2)

Reorder the terms:
-40 + 3x + x2 = 8(-2 + x)
-40 + 3x + x2 = (-2 * 8 + x * 8)
-40 + 3x + x2 = (-16 + 8x)

Solving
-40 + 3x + x2 = -16 + 8x

Solving for variable 'x'.

Reorder the terms:
-40 + 16 + 3x + -8x + x2 = -16 + 8x + 16 + -8x

Combine like terms: -40 + 16 = -24
-24 + 3x + -8x + x2 = -16 + 8x + 16 + -8x

Combine like terms: 3x + -8x = -5x
-24 + -5x + x2 = -16 + 8x + 16 + -8x

Reorder the terms:
-24 + -5x + x2 = -16 + 16 + 8x + -8x

Combine like terms: -16 + 16 = 0
-24 + -5x + x2 = 0 + 8x + -8x
-24 + -5x + x2 = 8x + -8x

Combine like terms: 8x + -8x = 0
-24 + -5x + x2 = 0

Factor a trinomial.
(-3 + -1x)(8 + -1x) = 0

Subproblem 1

Set the factor '(-3 + -1x)' equal to zero and attempt to solve: Simplifying -3 + -1x = 0 Solving -3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 0 + 3 -1x = 0 + 3 Combine like terms: 0 + 3 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3

Subproblem 2

Set the factor '(8 + -1x)' equal to zero and attempt to solve: Simplifying 8 + -1x = 0 Solving 8 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -1x = 0 + -8 -1x = 0 + -8 Combine like terms: 0 + -8 = -8 -1x = -8 Divide each side by '-1'. x = 8 Simplifying x = 8

Solution

x = {-3, 8}

See similar equations:

| 2.5+14.1k=3.6k | | 3-3.7b=10.3b | | 98x^3/y^5 | | 17x-20-7x=2(6x-4) | | 265-x=200 | | 1-3m=-17 | | 5q+4=8q-5 | | 4k^2+8k=0 | | -8d-5d+7d=71 | | 18+b=x | | 5x21/2 | | -r-4=-2 | | 2a-(5/a-1)=0 | | 99n+4=40 | | 5x-13=38 | | 3u-3=3u-6 | | 0=p+19 | | x-35=0 | | F(k+2)=3(2)+7 | | 21/26y=7 | | 23=23+x | | 0=4x^2+79x+376 | | y=1.3(-8)-8 | | -23=8(u+2)+5u | | 9x-3(x+5)=5x+9-3x | | x/10+1/3=x/5+1/2 | | -p=7/4 | | 4r-2=-6 | | 3y+2x=180 | | y=1.3(-8)(-8) | | 3x+7=180 | | x-1=3x-2 |

Equations solver categories